2019
DOI: 10.3892/ijmm.2019.4303
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an eight-lncRNA prognostic model for breast cancer using WGCNA network analysis and a Cox‑proportional hazards model based on L1-penalized estimation

Abstract: An ever-increasing number of long noncoding (lnc) RNAs has been identified in breast cancer. The present study aimed to establish an lncRNA signature for predicting survival in breast cancer. RNA expression profiling was performed using microarray gene expression data from the National Center for Biotechnology Information Gene Expression Omnibus, followed by the identification of breast cancer-related preserved modules using weighted gene co-expression network (WGCNA) network analysis. From the lncRNAs identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In order to predict the DEmRNA co-expressed lncRNA connected to survival, we performed the single factor Cox analysis by R package "survival" [50], risk model was calculated as previously reported [51]. According to the best risk model obtained by multivariate Cox analysis, the survival score was performed, and the average number of risk scores of each sample of TCGA-GBM data was also calculated.…”
Section: Single and Multivariate Factor Cox Analysis Roc And Survivamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to predict the DEmRNA co-expressed lncRNA connected to survival, we performed the single factor Cox analysis by R package "survival" [50], risk model was calculated as previously reported [51]. According to the best risk model obtained by multivariate Cox analysis, the survival score was performed, and the average number of risk scores of each sample of TCGA-GBM data was also calculated.…”
Section: Single and Multivariate Factor Cox Analysis Roc And Survivamentioning
confidence: 99%
“…Gene structures were drawn by GSDS v2.0 [50]. Motifs reported on SOX protein data via MEME v5.0.5 [51]. SOX secondary structure was built by Secondary structure by NPS@: Network Protein Sequence Analysis online service [52].…”
Section: Example: Genome-wide Retrieval and Identification Of Sox Genmentioning
confidence: 99%
“…Distinguished from other analysis method, WGCNA hierarchical clustering methods focused on the whole genome information instead of previous selected genes to overview of the signature of gene networks in phenotypes which can avoid bias and subject judgement 12 . Weighted Gene Co‐expression Network Analysis has been widely used in the study of multiple diseases 13–15 . By constructing a co‐expression network of genes and an identification module, WGCNA can investigate hub genes closely related to clinical phenotypes, which will provide us a beacon of hope for discovering new molecular biomarkers and therapeutic targets in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Since that study, various models have been constructed to predict prognoses in cancer patients. [46][47][48] Nevertheless, there have been few prediction models combining lncRNA information with CRC clinical features. In our study, we identified a prognostic model with two CRC lncRNAs, and we constructed a nomogram and risk classification system.…”
Section: Discussionmentioning
confidence: 99%